Benefits satisfaction amongst employees in local educational institutions. - Chua, Xin Fang. (2013)
This paper investigates the impact of types of benefits on the satisfaction level of employees. The result of the study is mediated by benefits value of appraisal accuracy and procedural justice which is in turn moderated by the nationality of the employees. In this study, a total of three hypotheses were formed.